Evaluate sustainable human resource management in the manufacturing companies using an extended Pythagorean fuzzy SWARA-TOPSIS method - Saeidi, Parvaneh (2022)
Today, organizations realized the importance of sustainability in concern with their business activities. They found out that they should focus on other aspects such as environmental and social and economic sustainability. Lately, Sustainable Human Resource Management (SHRM) is introduced as an instrument to indicate that HRM can affect the sustainable development and resource preservation of organizations. Despite that, SHRM and its related subjects are still in an emerging phase. The present study aims to propose a comprehensive approach to examine the main important factors of SHRM. To do so, a survey approach with the literature review interviewsview with experts is carried out to classify, rank, and evaluate the key SHRM factors in the manufacturing companies in Ecuador. In order to assess and prioritize the factors and the alternatives, this paper introduces a new approach using an integrated Stepwise Weight Assessment Ratio Analysis (SWARA)- Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method on the Pythagorean fuzzy sets (PFSs) setting called the PF-SWARA-TOPSIS method. To do this, we extend the SWARA method to identify and rank the SHRM factors by using PFSs. Afterward, to assess and prioritize the alternatives, this study utilizes the TOPSIS approach under PFSs. Next, to show the efficacy and applicability of the developed framework, a real case study of the SHRM problem is discussed on PFSs. Furthermore, this study performs a sensitivity investigation over diverse sets of criteria weights to illustrate the advantages of the proposed methodology. The investigation results demonstrate that the green work-life balance was ranked as the first factor by following corporate social responsibility, green employee relations, and business process redesign factors. Finally, the results of this study found that the developed approach has high efficacy and capability to handle the SHRM problem in manufacturing companies.